What do Klein et al. tell us about test scores in Texas? - Toenjes, Laurence A. (Education Policy Analysis Archives, 2005)
A paper appearing in this journal by Klein, Hamilton, McCaffrey and Stecher (2000) attempted to raise serious questions about the validity of the gains in student performance as measured by Texas' standardized test, the Texas Assessment of Academic Skills (TAAS). Part of their analysis was based on the results of three tests which they administered to 2,000 fifth grade students in 20 Texas schools. Although Klein et al. indicated that the 20 schools were not selected in a way which would insure that they were representative of the nearly 3,000 Texas schools that enrolled fifth graders, generalizations based upon the results for those schools were nonetheless offered. The purpose of this short paper is to demonstrate just how unrepresentative the 20 schools used by Klein et al. actually were, and in so doing to cast doubt on certain of their conclusions.